SUSTAINABILITY: FLOOR WATERPROOFING FEASIBILITY STUDY AND RAINWATER REUSE IN A TEXTILE INDUSTRY : SUSTENTABILIDADE: ESTUDO DE VIABILIDADE DE IMPERMEABILIZAÇÃO DE PISOS E REUTILIZAÇÃO DE ÁGUA DE CHUVA EM UMA INDÚSTRIA TÊXTIL - Rodrigues, Thales Volpe; Queiroz, Lucas Marcos Silva; Sanjulião, Lo-Ruana Karen Amorim Freire; Santos Filho, Vitor Hugo (Brazilian Journal of Production Engineering, 2020)
This work addresses the importance of the conscious use of water in the business environment, a theme that has been the target of great repercussion in the organizational environment, focusing mainly on the aspects of rainwater reuse and the reduction of its consumption in the process through waterproofing. The objective of the work is to minimize production costs with environmental responsibility. Through meteorological studies, a satisfactory rate of rain was identified in the region where the company is located, allowing rainwater harvesting to be used in production. Subsequently, the study was carried out to make the catchment project viable, which, after management approval, a pilot test was developed to measure the results of rainwater reuse. A small area of ​​the floor was waterproofed to assess the infiltration rate. It was thus identified that, in the months of greater precipitation, the company becomes self-sufficient in the use of water, this is due to the waterproofing of the floor with epoxy paint, which had significant and consistent effects as expected. As a result of satisfactory testing, training was provided to raise employee awareness. The project is undergoing simulations and it is estimated that the results are significant for the company.